Fiscal Adjustment in the Context of Growth and Equity, 1986-1996 - Rosario G. Manasan (Philippine Institute for Development Studies (PIDS), 1998)
Evidences from the recent Philippine fiscal position indicate severe constraint in the government's option to support economic recovery, sustainable growth and poverty alleviation. This has left the government no alternative but to subsume to the IMF auspices. From 1986 to 1996, indicators of economic performance have been favorable. Despite this, several questions regarding the country's fiscal health continue to loom policymakers. This paper reviews the growth in the size and the changing composition of national government revenues in 1986-1995 and evaluates recent changes in tax structure and administration with respect to revenue adequacy, economic efficiency and equity. It also appraises changes in the size and composition of government expenditures with respect to their possible impact on growth and equity. In addition, it reviews the evolution of the fiscal position of the consolidated public sector and assesses its long-term sustainability and implications.
Keywords: 330; tax buoyancy; tax structure; tax measures; effective tax rates; government revenue; fiscal deficit